THE MULTIFACETED SCHOOL: DO TEACHING IN PARTNERSHIP WITH THE COMMUNITY. A STUDY IN A SCHOOL IN THE HEARTLAND OF THE PROVINCE OF CHACO - María Acuña Zenoff; Silvia Grinberg (Universidad Nacional del Nordeste, 2018)
In this article we try to address the ways of "teaching" in a school in the interior of the province of Chaco that, over time, became a multifaceted space, having to launch new dynamics, understandings and practices, in a context in which their school population began to mutate very rapidly. It was the only secondary school that, in a very short period (2001-2016), as the town grew, began to receive migrant students from rural areas. This resulted from new logics in the use of land that, in a constant way, expelled the rural working population from the countryside. We hypothesize that, as part of these reconfigurations, the school became a multifaceted space in the face of the need to build alternatives that would sustain a new enrollment of young people that entered the school, this involved in a key way the partnership with the community to attend to the daily urgencies. We ask ourselves, therefore, about the search for alternatives, strategies and for the set of transformations of the school ground, as narrated by the actors and in the description of the processes of reconfiguration of school life, focusing the view on the dynamics that He assumed doing daily. We understand that, in times of crisis and reconfiguration, the school and its teachers enable multiple spaces from the possibility and daily urgencies and the "doing teaching" is inevitably crossed by historical conditions in which subjects must be reconfigured, to the pair of the vertiginousness of the scenarios in which they are mobilized.